2022 IRI CTO Forum Summary: The 2022 IRI CTO Forum identified key issues facing CTOs in a VUCA world and specific actions they can take to address them. Issue 1 (2nd January 2023) - Bernstein, Ed; Euchner, Jim
Abstract : Overview: Innovation Research Interchange's (IRI) 2022 in-person meeting of chief technology officers was held in Washington, DC, on September 19–20, 2022. Craig Slavtcheff, executive vice president – chief technology and innovation officer of Campbell Soup Company, hosted the meeting. The CTO Forum took place in conjunction with the National Association of Manufacturers Board of Directors meeting. James Euchner, visiting professor at Aston Business School (UK) and editor-in-chief of Research-Technology Management ( RTM ), facilitated the meeting.